Correlation of the role of boron concentration on the microstructure and electrochemical properties of diamond electrodes. Issue 1 (2nd January 2021) - Chen, Yinhao; Gao, Xiaolei; Liu, Guoshuai; Zhu, Ruitong; Yang, Wanlin; Li, Zhishen; Liu, Fangmu; Zhou, Kechao; Yu, Zhiming; Wei, Qiuping; Ma, Li
Abstract: In this article, a series of highly boron-doped diamond ([B] > 10 21 cm −3 ) electrodes with small gradient variations in boron concentration were prepared by hot filament chemical vapor deposition (HF-CVD). Reactive blue 19 (RB-19) dye solution was used as a prototype wastewater. Interestingly, we found that the electrochemical properties (electrochemically active surface area and oxygen evolution potential) and the electrochemical degradation performance did not deteriorate linearly with increasing boron concentration. Specifically, the electrochemically active surface area of the electrode at [B]/[C] = 50, 000 ppm was the highest of 9.366 cm 2, the chromaticity removal rate of RB-19 dye wastewater reached 100% after 90 min, and the TOC removal rate reached 74.48% after 180 min with the lowest energy consumption.